Divine love : Luce Irigaray, Women, Gender, and Religion. - Joy, Morny (Manchester studies in religion, culture, and gender., 2006)
Divine love? explores the work of Luce Irigaray for the first time from the perspective of Religious Studies. The book examines the development of religious themes in Irigaray?s work from?Speculum of the Other Woman?, in which she rejects traditional forms of western religion, to her more recent explorations of eastern religions. Irigaray?s ideas on love, the divine, the ethics of sexual difference and normative heterosexuality are analysed and placed in the context of the reception of her work by secular feminists such as Judith Butler, Drucilla Cornell and Elizabeth Grosz, as well as by fe.